Translation Theory and Legal Translation - Dr. Suha M. J. Khaffaf (PROSPECTIVE RESEARCHES, 2023)
In our age of globalization and multilingualism there is a growing demand for competent legal translator. The work attempts to shed light on the sensitivity of legal texts, and how the translation should be reliable, i.e., it must produce the intended legal effects. The study hypothesizes that legal translation is recognized as an independent area of translation on equal footing with literary translation, religious translation and technical/scientific translation. The study starts with viewing some misleading ideas by translation theorists about translating legal texts. Then text typologies for translation are fully discussed. The function of legal texts is identified followed by a detailed discussion of legal translation; translation and text type. Finally, the status of legal translation is evaluated on the bases of the recent translation theories, i.e. Hermeneutics. The paper comes up with some conclusions; the most important of which are that translation theory and legal translation are intertwined and a successful legal translator must develop an interdisciplinary approach to the subject, thus that any theoretical approach to legal translation must take account of the legal factors of the particular communicative situation in the mechanism of law.